The impact of fundamental and financial traders on the term structure of oil - Thomas Heidorn; Frieder Mokinski; Christoph Rühl; Christian Schmaltz (Frankfurt School of Finance & Management, 2014)
We study how the exposure of fundamental and financial traders affects the futures curve of WTI oil and the market integration between WTI and Brent as measured by their price spread. To obtain a parsimonious representation of the futures curve, we decompose it into a level-, a slope- and a curvature factor. In a second step, we separately regress each extracted factor on measures of the market exposure of fundamental and financial traders revealing whether and how the exposure of the two trader groups affects the different dimensions of the futures curve. Spanning from 2006 until 2012, our dataset covers sub-periods of a sharp WTI-price rise as well as a diverging Brent-WTI-spread. Our contribution is threefold: First, we suggest that it is important to distinguish between level and slope as we find that fundamental traders have a measurable impact on the level of the futures curve, but do not play much of a role for its slope or curvature, whereas the exposure of financial traders mainly influences the slope of the futures curve. Despite allegations to the contrary, we find no evidence of a systematic impact of non-fundamental traders on the level of the futures curve, for example during the 2006-2008 oil price surge. Second, we suggest using relative short- and relative long positions for fundamental and financial traders instead of the net position as the former reflect better the overall group exposure and yield more significant results. Third, we find that the exposure of financials is the key driver of the Brent-WTI spread. It confirms that financial rather than fun-damental traders are responsible for integrating the two markets.
Keywords: Q40; G13; 330; WTI; Price speculation; Oil price rise; Market Integration